2023
DOI: 10.1002/1873-3468.14593
|View full text |Cite
|
Sign up to set email alerts
|

The Bcl‐2 family protein bid interacts with the ER stress sensor IRE1 to differentially modulate its RNase activity

Abstract: IRE1 is a transmembrane signalling protein that activates the unfolded protein response under endoplasmic reticulum stress. IRE1 is endowed with kinase and endoribonuclease activities. The ribonuclease activity of IRE1 can switch substrate specificities to carry out atypical splicing of Xbp1 mRNA or trigger the degradation of specific mRNAs. The mechanisms regulating the distinct ribonuclease activities of IRE1 have yet to be fully understood. Here, we report the Bcl-2 family protein Bid as a novel recruit of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Several cytosolic inhibitors, positive modulators, and post-translational modifiers of IRE1α have been identified. While Bax inhibitor-1 (TMBIM6) [49], fortilin [50], and BID [51] were identified as inhibitors, the BCL-2 family members BAX and BAK [52] can act as positive modulators. Moreover, it has been shown that the stability and activity of IRE1α can be modified by post-translational modifications like phosphorylation [53] or ADP-ribosylation [54].…”
Section: Discussionmentioning
confidence: 99%
“…Several cytosolic inhibitors, positive modulators, and post-translational modifiers of IRE1α have been identified. While Bax inhibitor-1 (TMBIM6) [49], fortilin [50], and BID [51] were identified as inhibitors, the BCL-2 family members BAX and BAK [52] can act as positive modulators. Moreover, it has been shown that the stability and activity of IRE1α can be modified by post-translational modifications like phosphorylation [53] or ADP-ribosylation [54].…”
Section: Discussionmentioning
confidence: 99%
“…All these proteins help in amplifying the IRE1 signal during ER stress. Other proteins like Fortilin (Pinkaew et al, 2017), Bax inhibitor-1 (Lisbona et al, 2009), and Bid (Bashir et al, 2023) interact with IRE1 to inhibit its activity, while interaction with Nck, TNFR-associated factor 2 (TRAF2) (Luo et al, 2008;Nguyen et al, 2004), and RACK1 (Qiu et al, 2010) form the scaffolding interactions. Besides these physical interactions, IRE1 communicates with other cellular pathways, including the Akt/mTOR signalling pathway (Ozcan et al 2004, Qin et al, 2010, Wouters et al, 2008.…”
Section: Introductionmentioning
confidence: 99%